Checklist, Indeks Ekologi, dan Status Konservasi Komunitas Fauna Akuatik di Kawasan Sungai Unda dan Sekitar Pantai Jumpai, Kabupaten Klungkung, Provinsi Bali - Indrawan, Gede Surya; Wiradana, Putu Angga; Wijaya, I Made Saka; As-syakur, Abd. Rahman; Syahputra, M. Rheza Rizki; Wijana, I Made Sara (Bumi Lestari; Vol 21 No 1 (2021)DO - 10.24843/blje.2021.v21.i01.p02, 2021)
Aquatic organisms or nekton have an important role in supporting the stability of the aquatic environment and human life. This study aims to determine the nekton type community, ecological index, and their conservation status in the Unda River area and around Jumpai Beach, Klungkung Regency, Bali. The study was conducted in July - August 2020. The study was conducted in 2 communities, namely Macrozoobenthos and Nekton. Macrozoobenthos samples were collected using the quadratic method in the Jumpai Beach area and the direct observation method along the Unda River. Nekton communities are collected through primary data using "survey methods" and secondary data through interviews with fishermen and local communities. The ecological index data were analyzed using the Shannon-Weiner diversity index (H'), dominance index (C), and uniformity index (E), while the data on Nekton type and conservation status were analyzed descriptively. The nekton species community in the waters of the Unda River and Jumpai Beach areas was obtained as many as 26 species in 21 families which were dominated by Kepala Timah ( Aplocheilus panchax ) and sepat rawa ( Trichogaster trichopterus ), while Nautica sp for the Macrozoobenthos community. The ecological index of the aquatic community is the Shannon-Weiner Diversity Index (H') value of 2.98 (moderate), the wealth index (R) of 3.95 (moderate), and the evenness index (E) of 1.21. (High). The highest percentage ratio of nekton communities was obtained by the Macrozoobenthos community, namely 53%, while the nekton species was 46%. Conservation status shows that 13 species are included in the LC (Least Concern) category, 12 species are included in the NE (Not Evaluated) category, and 1 species are included in the VU (Vulnerable) category.